DNA source and primer choice affect the reliability of metabarcoding for nematode community profiling in agricultural soils - Jerry Akanwari; Md Rashedul Islam; Ping Liang; Tahera Sultana (PLoS ONE, 2026)
The advent of metabarcoding has greatly advanced our understanding of nematode ecology by overcoming many limitations associated with traditional morphology-based methods. The NF1–18Sr2b (NF1) is the standard and widely used primer pair to assess nematode communities. However, this primer also presents challenges, especially when applied to DNA extracted directly from soil, where it has been shown to underestimate species richness. Consequently, soil DNA extraction (SE) has been viewed as a less attractive option for metabarcoding studies. To explore whether nematode DNA extraction (NE) can serve as a viable option for metabarcoding studies, we compared two degenerate primer pairs, NemF–18Sr2b (NemF) and NemFopt–18Sr2bRopt (NemFopt) to NF1. The study used two DNA sources: NE, and SE derived from 10 g and 1.25 g of dry agricultural soils. Our findings indicate that the NemF and NemFopt primers yielded higher taxonomic resolution and species richness in both SE and NE compared to NF1. Specifically, NF1 detected only 2–4% of nematode sequences in SE and 69% in NE, whereas NemFopt detected the highest proportion, with 100% of nematode sequences in NE and >70% in SE. Although none of the primers amplified all taxa, NF1 was associated with higher undetected taxa. NemFopt in the 10 g SE identified nematode assemblages comparable to those from NE, suggesting that SE can effectively capture nematode communities similar to NE. Nematode community profiles and ecological indices were stable across soil DNA input volumes and DNA sources. Maturity index and enrichment index did not differ significantly between NE and SE. Community similarity across extraction methods varied with primer choice, with NemFopt showing the greatest consistency. Although this study was limited to two soil types, two field sites, and three primer sets, our results suggest that increasing primer specificity can reduce the amount of soil required for metabarcoding and make SE a viable option. Moreover, primer choice, soil type, and DNA source can significantly affect nematode diversity estimates and ecological interpretations, highlighting the need for primer standardization in nematode metabarcoding studies.